Four-Quadrant Operation of PMSM Drive Fed by a Matrix Converter - Aydogmus, Ontur; Sunter, Sedat (Ieee, 2011)
In this paper, a PMSM is fed by a matrix converter to perform four -quadrant operation. Combining a matrix converter and a PMSM results in an increase at the performance of the drive system. Especially, some of motor applications require motoring and regenerating operation such as cranes, hoists and lifts. Bi-directional power flow feature of the matrix converter is used for these type motor applications. In addition, the converter input current and output current waveforms are analyzed considering their harmonic spectra. This study has shown that the matrix converter is very effective solution for this type of motor applications.
International Aegean Conference on Electrical Machines and Power Electronics / Electromotion Joint Conference -- SEP 08-10, 2011 -- Istanbul, TURKEY
Keywords: Matrix converter; ac adjustable speed drive; regenerative operation; permanent magnet synchronous motor; vector control